INFLUENCE OF THE BOARD OF DIRECTORS, AUDIT COMMITTEE, MANAGERIAL OWNERSHIP ON FINANCIAL DISTRESS IN COMPANIES BASIC AND CHEMICAL INDUSTRY SECTORS - Deni Amelia; Silvia Iskandar; Fitrah Sari (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
This study aims to determine the influence of the Board of Directors, Audit Committee, Managerial Ownership, and Institutional Ownership on Financial Distress in Basic Industry and Chemical Companies Listed on the Indonesia Stock Exchange for the 2016-2019 Period. The data used is sourced from financial data on the Indonesia Stock Exchange through the website www.idnfinancials.com. And a selection has been made based on predetermined criteria. The population used in this study was 68 companies in the Basic Industry and Chemical Sector. By using purposive sampling, the sample obtained was 11 companies. With this research, it is hoped that it can become a science to help further researchers as well as students or the general public who need a source of information. From this study, it can be seen that the Board of Directors, Audit Committee, Managerial Ownership, Institutional Ownership do not significantly influence financial distress in the Basic Industry and Chemical Sector Companies. But all variables affect simultaneously. The selection of sectors in this study is because these stocks are currently the most popular. The Basic Industry and Chemical sectors represent basic elements used in everyday life. Almost all items that we use every day are products of basic industrial companies and chemicals. Keywords: Board of Directors, Audit Committee, Managerial Ownership, Institutional Ownership, Financial Distress